Implementation of Assessment Standards for Learning Outcomes at the Cendekia Mandiri Foundation: A Review from the Perspective of Quality Assurance and Quality Control in Community Education - Anggala Regina Br. T; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article aims to analyze the implementation of assessment standards on learning outcomes as part of quality assurance and quality control in community education at Yayasan Cendekia Mandiri. This study used a qualitative approach with primary data collection methods through interviews with administrators and educators at Yayasan Cendekia Mandiri. The results of the study indicate that the implementation of assessment standards is carried out through formative and summative assessments covering cognitive, affective, and psychomotor aspects of learners. The implementation of assessment standards helps educators monitor the development of learners’ learning outcomes more systematically, improve the effectiveness and quality of the learning process, and support the implementation of more structured and sustainable learning evaluations. In addition, the implementation of assessment standards also plays an important role in supporting the implementation of quality assurance and quality control systems in community education at Yayasan Cendekia Mandiri.